2013
DOI: 10.3102/0162373713482763
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Professional Development to Promote the Diffusion of Instructional Expertise Among Teachers

Abstract: This study examines how high-quality professional development can promote the diffusion of effective teaching strategies among teachers through collaboration. Drawing on longitudinal and sociometric data from a study of writing professional development in 39 schools, this study shows that teachers' participation in professional development is associated with providing more help to colleagues on instructional matters. Further, the influence of professional development on participants' instructional practice dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 63 publications
3
95
0
8
Order By: Relevance
“…The affect that teachers of color have not only relates to their own students' learning but can also influence their colleagues' beliefs and practices (Sun, Loeb, & Grissom, 2017;Sun, Penuel, Frank, Gallagher, & Youngs, 2013). For instance, since teams of teachers collectively contribute to student learning outcomes, the presence of a teacher of color in a teaching team may resocialize other teachers to increase their cultural awareness and to change their interactions with minority students (Grissom et al, 2015).…”
mentioning
confidence: 99%
“…The affect that teachers of color have not only relates to their own students' learning but can also influence their colleagues' beliefs and practices (Sun, Loeb, & Grissom, 2017;Sun, Penuel, Frank, Gallagher, & Youngs, 2013). For instance, since teams of teachers collectively contribute to student learning outcomes, the presence of a teacher of color in a teaching team may resocialize other teachers to increase their cultural awareness and to change their interactions with minority students (Grissom et al, 2015).…”
mentioning
confidence: 99%
“…In fact they benefited more when they participated in professional learning in a collaborative form (Cloonan 2009;Kopcha 2012) and when their school contexts and needs had to be considered (Stein et al 1999). In much of the literature, teachers' learning community and network building were highlighted (Scribner et al 1999;Sun et al 2013). In the context of diffusion of innovation, Dearing et al (2011) proposed the idea of an ''implementation registry'' in the domain of healthcare, which was an online resource for practitioners within or across different institutions for sharing knowledge about solutions to challenges during dissemination, diffusion and implementation of an innovation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sun, Penuel, Frank, Gallagher, and Youngs (2013) found that teachers were able to diffuse learning from PD through their school when helping or supporting other teachers.…”
Section: Contextmentioning
confidence: 99%
“…In an effort to better understand the current state of PD, Wei, Darling-Hammond & Adamson, (2010) Recent research has expanded the idea of PD learning to include not just what happens in workshops or meetings, but also to include learning that takes place through interactions among educators. Sun, Penuel, Frank, Gallagher, and Youngs (2013) found that the learning potential of PD can be expanded through teacher interactions and sharing. In their study of a writing professional development in 39 schools, they found that teachers extended the influence of PD by using learning to support and help colleagues.…”
Section: Collective Participationmentioning
confidence: 99%